ANALISIS EFISIENSI KOPERASI PEGAWAI NEGERI REPUBLIK INDONESIA DI KABUPATEN JEMBRANA - Putri Anggreni; Vina Budi Agustiani (Forum Manajemen, 2021)
Cooperatives are economic institutions of the people who move the economy in promoting the welfare of the people of society. The main purpose of this study is to determine the level of efficiency and performance and cooperation of civil servants existing in Jembrana district. Data used in this research is secondary data obtained from PKPRI. KPRI population in Jembrana, while the number of samples used is 5 KPRI taken by simple random sampling. The research method used is Data Envelopment Analysis (DEA). Capital cost, management, number of managers as variable input, whereas Sisa Hasil Usaha (SHU) as output variables. Results of analysis states that KPRI-KPRI cause of these inefficiencies derived from inputs that do not conform with the needs/going waste. Cost management becomes the biggest cause of inefficiency in the cooperative that is equal to 2,65 %, followed by the number of managers amounted to 0,81% and 0,81% of capital. There were 1 of 5 KPRI KPRI samples were low, There were 1 of 5 KPRI samples that have not been efficient, there are: Shad Karya KPRI: 95,93%. Suggestion for KPRI is not efficient should pay more attention to the use of inputs in order to achieve maximum output, especially the allocation of operational costs so that more attention, use of employees' needs and improve its work, and reduce the use of funds derived from loans and optimize the rotation of capital and refers to other KPRI has achieved efficiently.